Potential bioactivity of Phoenix dactylifera fruits, leaves, and seeds against prostate and pancreatic cancer cells - Ghazzawy, Hesham S.; Gouda, Mostafa M.; Awad, Nabil S.; Al-Harbi, Nadi Awad; Alqahtani, Mesfer M.; Abdel-Salam, Maha M.; Abdein, Mohamed A.; Al-Sobeai, Sanad M.; Hamad, Asmaa A.; Alsberi, Hassan M.; Gabr, Gamal A.; Hikal, Dalia M. (Frontiers in Nutrition, 2022)
The use of functional foods’ phytochemicals in the chemoprevention of different cancer diseases be-come one of the hot scientific areas in the clinical nutrition field. For instance, Khalas palm cultivar (KPC; Phoenix dactylifera) is one of the natural sustainable resources that have high bioactivity and functionali-ty. This study aimed to investigate the antiproliferative activity and mode of action of KPC's different parts on the prostate (Pc3) and pancreatic (panc1) cancer cells at molecular level. In the methods, KPC's leaves, seeds, and fruits chemical composition and phytochemical analysis were analyzed. Also, the cy-totoxic effects of each extract were assessed against pc3 and panc1 cell lines. Besides, induction of apop-tosis, cell cycle analysis, and gene expression of both Cap3 and Cap9 were studied. The obtained results indicated that KPC leaves extract exhibited the highest significant (P < 0.01) anti-proliferation activity against the utilized cancer cell lines compared to fruits and seeds extracts. Also, there were significant (P < 0.05) differences in the phenolic contents, flavonoid of compounds, and antioxidant power of the leaves when compared to the seeds and fruits. Additionally, the highest cytotoxic effect (lowest IC50) was rec-orded with leave extract than seeds and fruits. Meanwhile, the seeds extract induced (P < 0.05) the apopto-sis and arrested cells in the G2/M phase as well as up-regulated the gene expression of the apoptot-ic-related genes (Casp3 and Casp9) compared to the control group. In conclusions, this study showed that the presence of bioactive components in the KPC different parts extracts have the significant ability to in-duce the apoptotic pathway that could down-regulate the proliferation of prostate (pc3) and pancreatic (panc1) cancer cells. The pathway mechanism of action was induced by the phytol molecule which pre-sented in its leaves extract.